Predicting leisure participation of school‐aged children with cerebral palsy: longitudinal evidence of child, family and environmental factors. Issue 3 (8th June 2012) - Bult, M. K.; Verschuren, O.; Lindeman, E.; Jongmans, M. J.; Westers, P.; Claassen, A.; Ketelaar, M.
Abstract Objective This longitudinal study aims to determine which child, family and environmental variables measured at 2 years of age predict leisure participation in formal and informal activities in school aged children with cerebral palsy (CP). Methods Parents of 46 children with CP (mean age at baseline: 2 years 6 months, SD 0 years 1 month; at follow‐up 6 years 7 months, SD 0 years 9 months; n = 26 boys, n = 20 girls; Gross Motor Classification System I = 30%, II = 7%, III = 28%, IV = 24%, V = 11%) completed the Children's Assessment of Participation and Enjoyment indicating their child's participation. Multivariate regression models were used to identify early predictors of participation. Results Movement ability was a significant child‐related predictor for formal activities (R2 17%, P < 0.05). Movement ability and social skills were most predictive (R2 62%, P < 0.00) for informal activities. The feeling of being restricted in family participation was the single most predictive factor for formal and informal activities at family level (R2 12%, P < 0.05, R2 25%, P < 0.05). Type of daycare was the only environmental variable that was predictive, and only for informal activities (R2 16%, P < 0.05). In the overall model movement ability was most predictive for leisure participation in formal activities (R2 17%, P < 0.05). Movement ability and social skills are the most important predictors for informal leisure participation (R2 62%, P < 0.01). Conclusions Several variables are found to be related to formal and informal participation at age 6. Movement ability and social skills at age 2 are most predictive of leisure participation when the child is 6 years old.